PTHrP regulation and calcium balance in sea bream (Sparus auratus L.) under calcium constraint - Abbink, W. (2006)
Juvenile gilthead sea bream were exposed to diluted seawater (2.5‰ salinity; DSW) for 3·h or, in a second experiment, acclimated to DSW and fed a control or calcium-deficient diet for 30·days. Branchial Ca2+ influx, drinking rate and plasma calcium levels were assessed. Sea bream plasma parathyroid hormone related protein (sPTHrP) was measured, and mRNAs of pthrp, its main receptor, pth1r, and the calcium-sensing receptor (casr) were quantified in osmoregulatory tissues and the pituitary gland. When calcium is limited in water or diet, sea bream maintain calcium balance; however, both plasma Ca2+ and plasma sPTHrP concentrations were lower when calcium was restricted in both water and diet. Positive correlations between plasma sPTHrP and plasma Ca2+ (R2=0.30, N=39, P<0.05), and plasma sPTHrP and body mass of the fish (R2=0.37, N=148, P<0.001) were found. Immunoreactive sPTHrP was demonstrated in pituitary gland pars intermedia cells that border the pars nervosa and co-localises with somatolactin. In the pituitary gland, pthrp, pth1r and casr mRNAs were downregulated after both short- and long-term exposure to DSW. A correlation between pituitary gland pthrp mRNA expression and plasma Ca2+ (R2=0.71, N=7, P<0.01) was observed. In gill tissue, pthrp and pth1r mRNAs were significantly upregulated after 30·days exposure to DSW, whereas no effect was found for casr mRNA expression. We conclude that in water of low salinity, declining pituitary gland pthrp mRNA expression accompanied by constant plasma sPTHrP levels points to a reduced sPTHrP turnover and that sPTHrP, through paracrine interaction, is involved in the regulation of branchial calcium handling, independently of endocrine pituitary gland sPTHrP.